Effects of Genotype and Child Abuse on DNA Methylation and Gene Expression at the Serotonin Transporter - Vijayendran, Meeshanthini; Beach, Steven; Plume, Jeffrey M.; Brody, Gene; Philibert, Robert (Frontiers in Psychiatry, 2012)
Altered regulation of the serotonin transporter (SLC6A4) is hypothesized to be a key event in many forms of neuropsychiatric illness, yet our understanding of the molecular mechanisms through which changes in gene function could lead to illness remains incomplete. In prior studies, we and others have demonstrated that methylation of CpG residues in the promoter associated CpG island alters SLC6A4 gene expression, that the extent of that DNA methylation in child abuse is genotype dependent, and that adverse childhood experiences such as child sex abuse are related to methylation. However, we have not examined whether these effects are splice variant specific, whether the association of methylation to gene expression varies as a function of genotype, and whether methylation in other SLC6A4 gene regions are more likely candidates for GxE effects. In the current investigation we measured methylation in lymphoblast DNA from 158 female subjects in the Iowa Adoption Studies at 16 CpG residues spread across the SLC6A4 locus, and analyzed their relationship to gene expression for two SLC6A4 splice variants. Methylation of two CpG residues in the shore of the CpG island (cg22584138 and cg05951817), a location immediately upstream from exon 1A, predicted gene expression for the splice variant containing Exon 1A + 1B. Methylation at two residues in the CpG island itself (cg 25769822 and cg05016953) was associated with total SLC6A4 expression. Examination of these four CpG residues indicated that methylation of cg22584138 was influenced by both genotype and sex abuse, whereas methylation of cg05016953 was influenced only by sex abuse history. Factors influencing methylation at other CpG dinucleotide pairs were not identified. We conclude that methylation effects on transcription may vary as a function of underlying gene motif and splice variant, and that the shore of CpG islands, upstream of TSS, may be of particular interest in examining environmental effects on methylation.